Predicted HLA Class I and Class II Epitopes From Licensed Vaccines Are Largely Conserved in New SARS-CoV-2 Omicron Variant of Concern - López, Daniel (Frontiers in Immunology, 2022)
The potential effect of emerging SARS-CoV-2 variants on vaccine efficacy is an issue of critical importance. In this study, the possible impact of mutations that facilitate virus escape from the cytotoxic and the helper cellular immune responses in the new SARS-CoV-2 Omicron variant of concern was analyzed for the 551 and 41 most abundant HLA class I and II alleles, respectively. Computational prediction showed almost all of these 592 alleles, that cover > 90% of the human population, contain enough epitopes without escape mutations in the emerging SARS-CoV-2 Omicron variant of concern. These data suggest that both cytotoxic and helper cellular immune protection elicited by currently licensed vaccines is virtually unaffected by the highly contagious SARS-CoV-2 Omicron variant of concern.